2020
DOI: 10.3389/fgene.2019.01296
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Hypothalamic Transcriptome Profiling Reveals the Reproductive Roles of mRNAs and miRNAs in Sheep

Abstract: Early studies have provided a wealth of information on the functions of microRNAs (miRNAs). However, less is known regarding their functions in the hypothalamus involved in sheep reproduction. To explore the potential roles of hypothalamic messenger RNAs (mRNAs) and miRNAs in sheep without FecB mutation, in total, 172 and 235 differentially expressed genes (DEGs) and 42 and 79 differentially expressed miRNAs (DE miRNAs) were identified in polytocous sheep in the follicular phase versus monotocous sheep in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 65 publications
2
23
1
Order By: Relevance
“…In the comparisons between FecB BB genotype and FecB ++ genotype, the number of DE mRNAs/lncRNAs were relatively lower than that observed in comparisons between follicular phase and luteal phase, implying that the FecB mutation have little in uence on transcription stability at mRNA/lncRNA levels in sheep oviduct probably. Contrary to present results, our previous transcriptomic research in sheep hypothalamus detected a remarkably greater number of DE mRNAs and miRNAs in the comparisons between two FecB genotypes [20], the difference in experimental tissues may be responsible for the results. 6 mRNAs and 1 lncRNA were obtained DE in both two comparisons, none research have been found focused on the relationships between these DE candidates and reproduction, thus, whether these genes participate sheep embryo development remains unclear.…”
Section: Transcriptomic Pro Lescontrasting
confidence: 99%
See 2 more Smart Citations
“…In the comparisons between FecB BB genotype and FecB ++ genotype, the number of DE mRNAs/lncRNAs were relatively lower than that observed in comparisons between follicular phase and luteal phase, implying that the FecB mutation have little in uence on transcription stability at mRNA/lncRNA levels in sheep oviduct probably. Contrary to present results, our previous transcriptomic research in sheep hypothalamus detected a remarkably greater number of DE mRNAs and miRNAs in the comparisons between two FecB genotypes [20], the difference in experimental tissues may be responsible for the results. 6 mRNAs and 1 lncRNA were obtained DE in both two comparisons, none research have been found focused on the relationships between these DE candidates and reproduction, thus, whether these genes participate sheep embryo development remains unclear.…”
Section: Transcriptomic Pro Lescontrasting
confidence: 99%
“…Results of the KEGG showed that majority of the enriched pathways were close related to metabolic pathways. Consistently, several metabolic pathways were also found enriched in the RNA-Seq research in sheep hypothalamus with different genotype [20]. However, TGFβ/BMP signaling pathway was not found enriched in both comparisons.…”
Section: Functional Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…Animals were from a core population of STH sheep in Luxi district of Shandong province, China. We collected jugular vein blood of healthy non-pregnant sheep aged 2-4 years (n=890), to identify the FecB genotypes using TaqMan probe [45]. Then, 12 sheep (6 MM and 6 ww, respectively) with no signi cant difference in age, weight, height, body length, chest circumference and tube circumference were selected for this experiment.…”
Section: Animals Preparationmentioning
confidence: 99%
“…Understanding the genetics of reproduction is important for the sheep industry, and recent researches have revealed that the regulation of litter size in sheep and goats is multiallelic and polygenic (Wang et al, 2019;Zhang et al, 2020). For example, FecB is a prominent gene affecting litter size, and ewes with the genotype of FecB BB carry two copies of a FecB mutation.…”
Section: Introductionmentioning
confidence: 99%